Isolated Loco-Regional Recurrence of Breast Cancer – Established and Innovative Therapy Concepts - Grischke, E.-M.; Wallwiener, D.; Souchon, R.; Fehm, T.; Loehberg, C. R.; Jud, S. M.; Lux, M. P.; Beckmann, M. W.; Renner, S. P. (Geburtshilfe und Frauenheilkunde, 2013)
The incidence of isolated loco-regional recurrence of breast cancer is between 2–20 %. It constitutes the most common type of breast cancer recurrence. In contrast to distant metastasis, a number of curative therapies are available to treat isolated loco-regional recurrence of breast cancer. Screening for early detection and regular examinations as part of a recommended follow-up programme is important. If distant metastasis has been excluded, therapy for recurrence ideally consists of surgery with R0 resection margins. Radiotherapy is indicated after non-curative surgery (R1/R2) for local tumour control to improve the chances of curative surgery and as a palliative therapy for local control of symptoms in inoperable cancer, also in combination with hyperthermia and systemic therapy. There was previously some uncertainty concerning the benefit of systemic therapy after R0 resection and breast-conserving therapy and after previous mastectomy. If the recurrence is hormone-receptor positive, (repeat) endocrine systemic therapy is indicated for both constellations. If the hormone-receptor status is negative, the question whether repeat chemotherapy is indicated as an adjuvant therapy and whether it offers a benefit to patients was still controversially discussed. However, data from the CALOR trial presented at the San Antonio Breast Cancer Symposium in 2012 has now answered this question in favour of chemotherapy. These new findings will not merely have an impact on future therapy recommendations but also on the entire clinical management of isolated loco-regional recurrence.
Keywords: breast cancer; local recurrence; chemotherapy